PENGARUH APLIKASI JENIS PUPUK ANORGANIK DENGAN EKSTRAK KEONG MAS TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora ex A. Froehner) - Asmono, Sepdian Luri; Pratama, Akhfin Putra; Rahmawati, Rahmawati; Arifiana, Nisa Budi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2026)
This study aims to determine the effect of the application of inorganic fertilizer types with golden apple snail extract on the growth of robusta coffee seedlings which was carried out at the Politeknik Negeri Jember Field from August 2023 to February 2024. The research method used was a Non-Factorial Randomized Block Design consisting of 4 treatment levels, namely P0 (control), P1 (Inorganic dose of 1g of Urea, 2g of TSP, 2g of KCl), P2 (golden apple snail extract application once every 4 weeks), and P3 (golden apple snail extract application once every 2 weeks Fertilization was carried out by pouring 200ml/polybag around the surface area of the coffee seedlings. The research data were analyzed using ANOVA with a further contrast test. The results of the 16 WAP (Weeks After Planting) study showed that the application of fertilizer types had a very significant effect on leaf chlorophyll content, leaf area, fresh weight, dry weight, and root length, but had no significant effect on seedling height and the number of leaf pairs. The use of fertilizer (P123) generally gave the best results on the parameters of leaf chlorophyll content, leaf area, fresh weight, dry weight, and root length of coffee seedlings. In the comparison of the application of golden snail extract, the application once every 2 weeks (P3) was effective in increasing dry weight. Meanwhile, the application of golden snail extract once every 4 weeks had the best value on the parameters of leaf area and fresh weight.